2021
DOI: 10.1080/00131911.2021.1984212
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perspectives on primary school pupils and sickness absence - exploring opportunities and challenges

Abstract: School absenteeism and its underlying causes can have negative effects on the cognitive, psychosocial and health development of a child. Research in primary education shows high rates of sickness absence. Many stakeholders are involved in addressing school absenteeism, including primary school professionals, child and youth healthcare physicians, school attendance officers and parents. This study explores these stakeholders’ perspectives, their approaches and what they envisage to be necessary in order to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Not covered. 1 Categorized under SAPs as the term is conceptualized as both problematic or nonproblematic authorized absence associated with physical, social, psychological, and lifestyle problems [58]. 2 Categorized under SAPs as the term is broadly conceptualized and used as a general term referring to unauthorized absenteeism [30,33,[36][37][38]47,51,61,62,64,68,70,72,73].…”
Section: Types Of Sapsmentioning
confidence: 99%
“…Not covered. 1 Categorized under SAPs as the term is conceptualized as both problematic or nonproblematic authorized absence associated with physical, social, psychological, and lifestyle problems [58]. 2 Categorized under SAPs as the term is broadly conceptualized and used as a general term referring to unauthorized absenteeism [30,33,[36][37][38]47,51,61,62,64,68,70,72,73].…”
Section: Types Of Sapsmentioning
confidence: 99%
“…Participating professionals worked for or with primary schools in either Amsterdam or West-Brabant region of the Netherlands and the parents had children in primary schools in West-Brabant. A comprehensive description of the methods of the interview study can be found in a separate article, which also includes results (11).…”
Section: Stakeholder Interviewsmentioning
confidence: 99%
“…Although it is authorized, frequent and/or longer periods of sickness absence should be addressed by schools. Such extensive sickness absence might be an indication of underlying problems and will have negative consequences for intellectual development and socio-emotional functioning (11,12). Thus, we start with the assumption that extensive sickness absence requires appropriate action by schools to improve pupils health in its broad sense.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus difficult to identify exact rates of absence due to illness on a national or even municipal level. Research suggests that absences due to illness account for a large proportion of total school absenteeism in primary education (Pijl et al, 2021;Roelofs et al, 2021). Nevertheless, there is sometimes less awareness of the impact of (authorised) illness-related absence on young people's well-being (Pijl et al, 2021).…”
Section: Challenges For School Personnel In Recording and Reporting A...mentioning
confidence: 99%
“…As a result, school personnel may respond to authorised absenteeism in a way which is 'too little, too late'. To be sure, authorised absence such as absenteeism due to illness accounts for a substantial share of total absenteeism among young people (Pijl et al, 2021;Roelofs et al, 2021). Moreover, authorised and unauthorised absenteeism both have the potential to affect a young person's development (Havik et al, 2015).…”
Section: Reporting Absenteeismmentioning
confidence: 99%